2017
DOI: 10.1038/ncomms15557
|View full text |Cite
|
Sign up to set email alerts
|

Exercise induces cerebral VEGF and angiogenesis via the lactate receptor HCAR1

Abstract: Physical exercise can improve brain function and delay neurodegeneration; however, the initial signal from muscle to brain is unknown. Here we show that the lactate receptor (HCAR1) is highly enriched in pial fibroblast-like cells that line the vessels supplying blood to the brain, and in pericyte-like cells along intracerebral microvessels. Activation of HCAR1 enhances cerebral vascular endothelial growth factor A (VEGFA) and cerebral angiogenesis. High-intensity interval exercise (5 days weekly for 7 weeks),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
314
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 370 publications
(369 citation statements)
references
References 54 publications
11
314
2
2
Order By: Relevance
“…Morland et al . () subsequently found that VEGF‐A had a pro‐angiogenic effect in both the hippocampus and sensorimotor cortex.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Morland et al . () subsequently found that VEGF‐A had a pro‐angiogenic effect in both the hippocampus and sensorimotor cortex.…”
Section: Resultsmentioning
confidence: 96%
“…; Morland et al . ). Both studies found that increased plasma lactate levels brought about by both exercise and systemic administration induced a comparable increase in brain vascular endothelial growth factor‐A (VEGF‐A) and their related signaling pathways.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…It is still unknown whether these factors might influence tumor progression, apoptosis, and metastasis. Exercise can also promote angiogenesis and knowing that the blood vessel walls contain a variety of stem cells (perivascular endothelial and mural cells) [134][135][136] and some of these stem cells have recently been show to have an inhibitory effect on cancer cells through unknown mechanisms, the beneficial effect of exercise on cancer development and prevention is maybe related to these blood vessel derived cells.…”
Section: Epigenetic Regulationmentioning
confidence: 99%